Pengaruh Digitalisasi UMKM, Persepsi Atas Informasi Akuntansi, dan Prinsip Going-Concern Terhadap Efektivitas Pelaporan Keuangan UMKM sesuai SAK EMKM - Pradnya, Putu Diah Pradnya Paramitha; Gede Adi Yuniarta (Universitas Pendidikan Ganesha, 2024)
The purpose of this study is to empirically examine the partial effects of digitalization of SMEs, perceptions of accounting information, and the going-concern principle on the effectiveness of financial reporting in accordance with SAK EMKM in SMEs in Buleleng Regency. The study used active SMEs that have been operating in Buleleng Regency for at least one year as research subjects. A quantitative approach was used, data were collected through questionnaires, analyzed using multiple linear regression analysis and hypothesis testing by SPSS version 20 for Windows. The sample was determined using the Purposive Sampling method, and 100 respondents were obtained. The results indicate that (1) digitalization of SMEs has no significant effect on the effectiveness of financial reporting in accordance with SAK EMKM, (2) perceptions of accounting information have a significant effect on the effectiveness of financial reporting in accordance with SAK EMKM, and (3) the going-concern principle has a significant effect on the effectiveness of financial reporting in accordance with SAK EMKM.